2007
DOI: 10.1093/jac/dkm219
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen is effective against Leishmania and induces a rapid alkalinization of parasitophorous vacuoles harbouring Leishmania (Leishmania) amazonensis amastigotes

Abstract: Tamoxifen effectively kills several Leishmania species and its activity against the parasite is increased by a modulation of the host cell intravacuolar pH induced by the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 34 publications
3
80
0
2
Order By: Relevance
“…11 However, use of human urine as a supplementary material for Leishmania and Trypanosome culture have been reported in many studies. [12][13][14][15] There is no information on the effects of urine on the infectivity of Leishmania parasites. Therefore, the aim of this study was to investigate the effects of culture medium containing human urine on the infectivity of different species of Leishmania parasites ( L. tropica , L. infantum , L. donovani , and L. major ).…”
Section: Introductionmentioning
confidence: 99%
“…11 However, use of human urine as a supplementary material for Leishmania and Trypanosome culture have been reported in many studies. [12][13][14][15] There is no information on the effects of urine on the infectivity of Leishmania parasites. Therefore, the aim of this study was to investigate the effects of culture medium containing human urine on the infectivity of different species of Leishmania parasites ( L. tropica , L. infantum , L. donovani , and L. major ).…”
Section: Introductionmentioning
confidence: 99%
“…8 In vitro effects of tamoxifen have also been established for fungal cells 9 and Leishmania parasites. 4 Having demonstrated the in vitro activity of tamoxifen against several species of Leishmania, we now show its effectiveness in vitro and in vivo against an L. braziliensis isolate obtained from a Brazilian patient with CL and on a L. chagasi reference strain.…”
Section: Discussionmentioning
confidence: 85%
“…3 We have previously shown that tamoxifen is active against several species of Leishmania in vitro. 4 Recently, we have also demonstrated that treatment of L. amazonensis-infected BALB/c mice with tamoxifen results in significant reductions in lesion and ulcer sizes, as well as in a sharp decrease in parasite burden. 5 In this work, we have focused on the investigation of tamoxifen efficacy in the treatment of leishmaniasis using two distinct rodent models to mimic CL and VL caused by L. braziliensis and L. chagasi, respectively.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations